2000
DOI: 10.1017/s0954102000000092
|View full text |Cite
|
Sign up to set email alerts
|

Predator–prey relationship between the nototheniid fish Trematomus bernacchii and the Antarctic scallop Adamussium colbecki at Terra Nova Bay (Ross Sea)

Abstract: Little information is available regarding predator-prey interactions in High-Antarctic coastal systems. In this study, the predation of Trematomus bernacchii (Pisces: Nototheniidae) on Adamussium colbecki (Mollusca: Pectinidae) is described and the related impact on the population structure of the mollusc is hypothesized. Fishes and scallops were collected during several expeditions between 1990/91 and 1997/98 summers, in nearshore waters at Terra Nova Bay (Antarctica). Adamussium colbecki was the main food it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…As A. colbecki is a suspension feeder, it represents a direct link between pelagic primary production and benthic or demersal higher level predators. Known predators of A. colbecki are T. bernacchii and invertebrates such as N. eatoni and Odontaster validus (Vacchi et al, 2000). According to our results, about 433 kJ m À 2 year À 1 (ca.…”
Section: Ecological Significancementioning
confidence: 54%
See 1 more Smart Citation
“…As A. colbecki is a suspension feeder, it represents a direct link between pelagic primary production and benthic or demersal higher level predators. Known predators of A. colbecki are T. bernacchii and invertebrates such as N. eatoni and Odontaster validus (Vacchi et al, 2000). According to our results, about 433 kJ m À 2 year À 1 (ca.…”
Section: Ecological Significancementioning
confidence: 54%
“…A. colbecki 'banks' play an important role in the coastal food web as they process up to 14% of the total carbon flux and represent an important food source for higher tropic levels, e.g. fish (Trematomus bernacchii Boulenger) and invertebrates such as Neobuccinum eatoni (Smith, 1875) and Paraborlasia corrugata (McIntosh, 1876) (Vacchi et al, 2000). Despite its widespread distribution and assumed significance for the system's energy flow (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The Antarctic Adamussium colbecki features the same active lifestyle in order to escape scouring icebergs and predators such as the fish Trematomus bernacchii and invertebrates (e.g. Neobuccinum eatoni, Paraborlasia corrugata) (Ansell et al 1998, Vacchi et al 2000, Peck et al 2004. A comparison of mature and immature Chlamys islandica showed that reduced CS activity and mitochondrial capacity caused a decrease in the aerobic capacity of adductor muscle in mature specimens and subsequently a delay in recovery after exhaustive swimming, which requires aerobic metabolism (Livingstone et al 1981, Brokordt et al 2000.…”
Section: Importance Of Maintenance Of Physiological Performance In Acmentioning
confidence: 99%
“…Baseline prey-predator-size relationships Vacchi et al (2000) established a preliminary predator-prey-size relationship between T. bernacchii and preyed A. colbecki, using 59 fish stomach contents:…”
Section: Study Area: Scallop and Fish Populationsmentioning
confidence: 99%
“…The only information available on this trophic link comes from a previous work by Vacchi et al (2000) that estimated a predator-prey-size linear relationship between T. bernacchii and A. colbecki, based on fishes' stomach contents. The innovative aspect of the present work relies on the application of this observed relationship to build a predictive probability model that estimates the preyed A. colbecki population-size distribution on the basis of the T. bernacchii population and its features (not taken into account in the previous work).…”
Section: Introductionmentioning
confidence: 99%